Intrapulmonary disposition of amphotericin B after aerosolized delivery of amphotericin B lipid complex (Abelcet; ABLC) in lung transplant recipients - Husain, Shahid; Capitano, Blair; Corcoran, Timothy; Studer, Sean M; Crespo, Maria; Johnson, Bruce; Pilewski, Joseph M; Shutt, Kathleen; Pakstis, Diana L; Zhang, Shimin; Carey, Mary Ellen; Paterson, David L; et al. (Transplantation, 2010)
Inhaled amphotericin preparations have been used for prophylaxis against invasive aspergillosis in lung transplant recipients. However, no published data exist regarding the pharmacokinetic profile of amphotericin B lipid complex in lung transplant recipients. We prospectively determined the concentrations of amphotericin B in the epithelial lining fluid (ELF) and plasma after aerosolized nebulization (AeroEclipse), of amphotericin B lipid complex at 1 mg/kg every 24 hr for 4 days in 35 lung transplant recipients. One brochoalveolar lavage sample and a simultaneous blood sample were collected at various time points after the fourth dose from each subject. High-performance liquid chromatography and high-performance liquid chromatography-MS-MS were used to measure amphotericin B. Concentrations of amphotericin B in ELF (median, 25-75 IQR) were at 4 hr (n=5) 7.20 μg/mL (1.3-17.6), 24 hr (n=6) 8.26 μg/mL (3.9-82.7), 48 hr (n=5) 2.15 μg/mL (1.4-5.5), 72 hr (n=4) 1.25 μg/mL (0.75-5.5), 96 hr (n=6) 0.86 μg/mL (0.55-1.4), 120 hr (n=4) 1.04 μg/mL (0.44-1.6), 144 hr (n=1), 4.25 μg/mL, 168 hr (n=3) 1.14 μg/mL, and 192 hr (n=1) 1 μg/mL. The plasma concentration of the drug remained below 0.08 μg/mL at all time points. During the study, the side effects noted included wheezing, coughing, and 12% decline in forced expiratory volume in 1 sec. We conclude that administration through aerosolized nebulization of amphotericin B lipid complex every 24 hr for 4 days in lung transplant recipients achieved amphotericin B concentrations in ELF above minimum inhibitory concentration of the Aspergillus nearly at 168 hr after the last inhaled dose and is well tolerated.